Analysis of glass injuries in a district hospital - Nzaumvila, Doudou kunda (My University, 2016)
Background and aim The Emergency Department (ED) of Embhuleni Hospital is used to see patients with glass-related injuries on a regular basis. This study aimed to compile and analyse data on glass injuries presenting to the ED of Embhuleni Hospital. Objectives The objectives of the study were to describe the demographic profile of patients presenting to the ED of Embhuleni Hospital with glass injuries, to determine the type of glass causing these injuries, to describe the characteristics of the injuries resulting from glass, to identify and describe the circumstances associated with different types of glass injuries, and to determine the social impact of glass injuries. Methods: This study was a prospective descriptive study. From the 1st of February 2013 to the 31st July 2013, the sample size that was used consisted of 104 participants. Descriptive statistics were used to assess the characteristics of the glass injuries. Results: Five different types of glass were reported as the causes of injuries, namely car glass (7.69 %), glass ampoules (3.85 %), glass bottles (82.69%), glass windows (3.85%) and street glass shards (1.92%). Glass bottle injuries were mainly caused by assaults (90.47 %), and the victims were mostly young males (80.23 %). The assaults occurred on alcohol-licenced premises in 65.11% of the cases. These injuries happened mostly over weekends (83.72 %) between 18:00 hours and 4:00 hours. The face (34.23 %) and the scalp (26.84 %) were the most affected body parts. Conclusion: Assault was the leading cause of glass injuries, especially on alcohol-licensed premises. Glass injuries generally resulted in minor lacerations with very few complications (2.68%). Key words: glass injury, district hospital.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment for the degree of MSc Med (Emergency Medicine) Head of Division of Emergency Medicine Faculty of Health Sciences Johannesburg 2015
Keywords: Glass Injuries